Knowing home. Book 1 : braiding Indigenous science with western science - Snively, Gloria; Williams, Wanosts'a7 Lorna; BC Open Textbook Project; BCcampus (University of Victoria, 2016)
"Since Indigenous peoples have developed time-proven approaches to sustaining both community and environment, Elders and young people are concerned that this rich legacy of Indigenous Science with its wealth of environmental knowledge and the wisdom of previous generations could disappear if it is not respected, studied and understood by today's children and youth. A perspective where relationships between home place and all other beings that inhabit the earth is vitally important to all residents - both inheritors of ancient Indigenous Knowledge and wisdom, and newcomers who can experience the engagement, joy and promise of science instilled with a sense of place. This book takes a step forward toward preserving and actively using the knowledge, stories, and lessons for today and future generations, and with it a worldview that informs everyday attitudes toward the earth. Knowing Home: Braiding Indigenous Science with Western Science is far more than a set of research papers or curriculum studies. The project outputs include both, but they are incorporated into a theoretical structure that can provide the methodological basis for future efforts that attempt to develop culturally responsive Indigenous Science curricula in home places. It is not just one or two angels to organize, but multiple interwoven approaches and cases that give this project its exceptional importance. Thus, the project outputs have been organized into two books. Book 1 provides an overview of why traditional knowledge and wisdom should be included in the science curriculum, a window into the science and technologies of the Indigenous peoples who live in Northwestern North America, Indigenous worldview, culturally responsive teaching strategies and curriculum models, and evaluative techniques. It is intended that the rich examples and cases, combined with the resources listed in the appendices, will enable teachers and students to explore Indigenous Science examples in the classroom; and in addition, support the development of culturally appropriate curriculum projects."--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Keywords: Ethnoscience -- Textbooks; Electronic books